Humani virusi papiloma pri abnormnih ploščatih in blago diskariotičnih celicah - Vrtačnik-Bokal, Eda (Zdravniški vestnik, 2003)
Background. A persistent infection with high-risk genotypes of human papillomaviruses (HPV) represents the most important etiologic factor for the development of cervical cancer, the second most frequent cancer in women in Slovenia as well as elsewhere in the world. in the detection of precancerous lesions the cervical Papanicolaou (Pap) smear screening is used in Slovenia and worldwide. Management of patients with repeat abnormal smears (Pap II) represents a great and complex clinical and public health problem; repeat cytologic examinations are the routine procedure in many countries, also in Slovenia, although the sensitivity of Pap smear testing in the detection of cervical intraepithelial neoplasms (CIN) II and III is relatively low. In cases of abnormal squamous cells and midlly dyskaryotic cells the presence of infections with high-risk HPV genotypes is being incresingly used as a complementary method to Pap smear testing. Methods and patients. In the study we enrolled 148 women who within two years had three subsequent Pap II smears (abnormal squamous cells or mildly dyskaryotic cells). The prevalence of HPV infections was determined using three molecular tests: Hybrid Capture II (HCII) (Digene Corporation, Gaithersburg, USA) and two variants of polymerase chain reaction (PCR-PGMY11/PGMY09 and PCR-CPI/CPIIG). HPV genotypes were determined using the method of enzyme restriction of PCR products multiplied by group-specific oligonucleotid primers PGMY11/PGMY09. Results. HPV infectionwas detected in 25.7% of women. In women aged -30 years (20.4%). Abstract truncated at 2000 characters.
Keywords: Carcinoma, Squamous Cell; Cervix Neoplasms; diagnostika; Epidemiology; Genotip; Genotype; ginekologija; Karcinom ploščatocelični; maternični vrat; Maternični vrat, novotvorbe; Papillomavirus, Human; papiloma virusi; Papilomavirus človeški; Polimerazna, verižna reakcija; Polymerase Chain Reaction; Prevalenca; Prevalence; rak (medicina); Sexually Transmitted Diseases, Viral; Spolno prenosljive bolezni virusne; Vaginal Smears; Vaginalni razmazi; virusne bolezni